Pengaruh Kepemimpinan, Komunikasi Dan Kompensasi Terhadap Kinerja Pegawai Pada Dinas Perhubungan Kabupaten Probolinggo - Imamatul Khoria; Joni Hendra; Yekti Rahajeng (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
The research was conducted on the Probolinggo Regency Transportation Service with the aim of knowing the influence of leadership, communication and compensation on employee performance at the Probolinggo Regency Transportation Service. The type of research used is quantitative with an associative approach. Sampling using saturated sampling. The sample in this research is 67 permanent employees. Sources of data used in this study come from primary data and secondary data. Data were collected through questionnaires and completed through data analysis methods in the form of validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination (r square) and partial hypothesis tests. The results showed that leadership had a positive and significant effect on employee performance, communication had a positive and significant effect on employee performance and compensation had a positive and significant effect on employee performance.